Autologous hematopoietic cell transplantation for multiple myeloma patients with renal insufficiency: A Center for International Blood and Marrow Transplant Research Analysis - Mahindra, Anuj (Bone Marrow Transplant, 2017)
Autologous hematopoietic cell transplantation (AHCT) in multiple myeloma (MM) patients with renal insufficiency (RI) is controversial. Patients who underwent AHCT for MM between 2008-2013 were identified (N =1492) and grouped as normal/mild (≥60 ml/min), N=1240, moderate (30-59), N=185 and severe RI (<30), N=67 based on MDRD. Multivariate analysis of non-relapse mortality (NRM), relapse, progression-free survival (PFS) and overall survival (OS) was performed. Of the 67 patients with severe RI, 35 were on dialysis prior to AHCT. Patients received melphalan 200 mg/m(2) (Mel200) in 92% (normal/mild), 75% (moderate) and 33% (severe) RI; remainder received 140 mg/m2 (Mel140). Thirty four of 35 patients with severe RI achieved post-AHCT dialysis independence. The 5-year PFS for normal, moderate and severe RI was 35 (95% CI, 31-38)%, 40 (31-49)% and 27 (15-40)% respectively, (p=0·42); 5-year OS for normal, mod and severe RI was 68 (65-71)%, 68 (60-76)% and 60 (46-74)% respectively, (p=0·69). With moderate RI, 5-year PFS for HDM 140 mg/m(2) was 18 (6-35)% and for Mel200 was 46 (36-57)% (p=0·009). With severe RI, 5-year PFS Mel140 was 25 (11-41) % and for Mel200 was 32 (11-58)% (p=0·37). We conclude that AHCT is safe and effective in patients with MM with RI.